Performance, Bone Parameters and Phosphorus Excretion of Broilers Fed Low Phosphorus Diets Supplemented with Phytase from 23 to 40 Days of Age - El-Sherbiny, A.E.; Hassan, H. M.A.; Abd-Elsamee, M.O.; Samy , A.; Mohamed, M.A.S. (International Journal of Poultry Science, 2010)
An experiment was conducted using 300 growing Ross 308 broilers from 23 to 40 days of age. Six dietary treatments were formulated. A basal diet contained 1.48% Dicalcium Phosphate (DCP) was used as a control diet (diet 1). Diets 2 and 3 contained 50% and 25% of the DCP of diet 1 (0.74 and 0.37%, respectively), while diet 4 was formulated without DCP. Diets 3 and 4 were fed without or with supplemented phytase enzyme (500 U/kg). Every dietary treatment was fed to 5 replicates (10 chicks each). The results showed no significant differences between birds fed diets containing 1.48 % DCP or 0.74% DCP on BWG, FI and FCR. Reducing dietary DCP level to 0.37% slightly decreased BWG compared with birds fed 0.74% DCP with inferior value of FCR. When DCP was removed from the diet BWG significantly (p